2018
DOI: 10.1371/journal.pone.0207435
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal structural analysis in eyes with diabetic retinopathy and diabetic macular edema—A novel OCT based imaging biomarker

Abstract: PurposeTo evaluate structural changes in the choroid among patients with diabetic macular edema (DME), with varying grades of diabetic retinopathy (DR), using enhance depth imaging spectral domain optical coherence tomography (EDI SD-OCT) scans.MethodsA cross-sectional study was conducted on 82 eyes with DR and DME and 86 healthy control eyes. Eyes with DME were classified according to the severity of DR as per the international DR severity scale. Sub foveal choroidal thickness (SFCT)was obtained using EDI SD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 30 publications
7
60
1
Order By: Relevance
“…In Gupta et al, we found that hypertensive patients had thinner choroid compared to non-hypertensive patients in the diabetic group. However, CVI was not affected by hypertension [17]. Moreover, in almost all studies mentioned in this article that investigated CVI, there was a significant decrease in CVI with worsening DR.…”
Section: In Diabetic Patients With and Without Dr Or Mementioning
confidence: 64%
See 2 more Smart Citations
“…In Gupta et al, we found that hypertensive patients had thinner choroid compared to non-hypertensive patients in the diabetic group. However, CVI was not affected by hypertension [17]. Moreover, in almost all studies mentioned in this article that investigated CVI, there was a significant decrease in CVI with worsening DR.…”
Section: In Diabetic Patients With and Without Dr Or Mementioning
confidence: 64%
“…Patients with hypertension were significantly found to have thinner SFCT when compared with non-hypertensive patients (319.0±54.6 μm vs. 354.0±48.8μm (P=0.01)). The presence of hypertension did not affect CVI [17].…”
Section: Studies Showing Increasing Ct In Dm Patients or With Worsenimentioning
confidence: 72%
See 1 more Smart Citation
“…However, they analyzed a smaller group of 38 eyes. Gupta et al 25 and Kim et al 36 showed that CVI was significantly decreased in eyes with worsening DR and DME compared with controls. Our current study demonstrated that patients with diabetes with a disease duration of more than 5 years had a decreased subfoveal CVI of Sattler's layer compared with those with shorter disease duration.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta and associates analyzed the structural choroidal changes occurring in patients with DR, concluding that subfoveal CT and CVI are dynamic parameters affected by diabetic macular edema [73]. Unlike CVI, subfoveal CT is also affected by ocular and systemic factors like edema and hypertension [73].…”
Section: In Diabetic Retinopathymentioning
confidence: 99%